The Influence in Ratio of Rice Husk and Polystyrene Foam on the Dehumidifying Absorbability of Lightweight Concrete Slab - Sergsiri, Supakit; Lawong, Amin; Sudsuansee, Thaitat; VongtaVee, Rachan (Kalasin University Journal of Science Technology and Innovation, 2024)
This research aimed to study the properties of lightweight concrete slabs using industrial and agricultural waste materials such as polystyrene foam and rice husk. Cement is mixed to produce lightweight concrete by casting it into concrete slabs for drying paddy and test plates of 30 x 30 x 5 centimeters and 5 x 5 x 5 centimeters. Hygroscopicity Test The results of the experiment showed that the slabs containing cement: polystyrene foam: rice husk in the proportions of 3:1:1, 3:2:0, and 3:0:2 increased the weight and strength of the test slabs, and the increased proportion of polystyrene foam mixed proportions reduced the weight of the slabs. The hygroscopicity of the test strips increases with the amount of husk mixed at proportions of 1:3:1, 1:2:2, and 1:1:3, respectively. Therefore, the right proportion that makes the slab lightweight is Formula 2, which is 1:2:2 (cement: polystyrene foam: rice husk) with a production cost of 67.722 baht per square meter.